The impact of Pseudomonas syringae type III effectors on transient protein expression in tobacco. (25th November 2014) - Buyel, J. F.; Buyel, J. J.; Haase, C.; Fischer, R.; Papen, H.
Abstract The production of recombinant proteins in plants is often achieved by transient expression, e.g. following the injection or vacuum infiltration of Agrobacterium tumefaciens into tobacco leaves. We investigated the associated plant defence responses, revealing that callose deposition is triggered by T–DNA transfer and that subsets of secondary metabolites accumulate in response to mechanical wounding or the presence of bacteria. We also tested the ability of five co‐expressed type III effector proteins from Pseudomonas syringae to modulate these defence responses and increase the yield of two model proteins, the fluorescent marker DsRed and monoclonal antibody 2G12. HopF2 and AvrRpt2 induced necrotic lesions 5 days post‐injection (dpi) even at low doses (OD600 nm = 0.0078), and increased the concentration of certain secondary metabolites. HopAO1 significantly reduced the number of callose deposits at 2 dpi compared to cells expressing DsRed and 2G12 alone, whereas HopI1 reduced the concentration of several secondary metabolites at 5 dpi compared to cells expressing DsRed and 2G12 alone. Co‐expression with HopAO1, AvrPtoB or HopI1 increased the concentrations of DsRed and 2G12 increased by ~6% but this was not a significant change. In contrast, HopF2 and AvrRpt2 significantly reduced the concentrations of DsRed and 2G12 by 34% and 22%, respectively. Our results show that type III effector proteins can modulate plant defence responses and secondary metabolite profiles but that transient co‐expression is not sufficient to increase the yields of target recombinant proteins in tobacco.